Dynamics of Labour and Capital Adjustment : A Comparison of Germany and the Netherlands - Michael Polder; Sher Verick (Institute for the Study of Labor (IZA), 2004)
In this paper we investigate the dynamic adjustment of labour and capital in German and Dutch firms. The Dutch labour market is characterised by greater flexibility in wages and work arrangements in comparison to Germany. These institutional differences imply that employment dynamics in the two countries should differ, and in particular, labour adjustment in the Netherlands should be more responsive to economic changes. On the other hand, there is unlikely to be such a divergence in capital dynamics as investment conditions are similar. Our results are consistent with this hypothesis. Furthermore, there is no evidence that labour market regulations in the two countries affect the dynamics of capital adjustment.
Keywords: E24; E22; C23; 330; investment; labour demand; interrelation; panel data; GMM; Investition; Arbeitsnachfrage; Arbeitsmarktflexibilisierung; Wirtschaftliche Anpassung; Vergleich; Deutschland; Niederlande